Investigation of the superconducting gap structure in κ-(BEDT-TTF)2Cu(NCS)2 and κ-(BEDT-TTF)2Cu[N(CN)2]Br by means of thermal-conductivity measurements. (1st September 2017) - Kühlmorgen, S; Schönemann, R; Green, E L; Müller, J; Wosnitza, J
Abstract: We report temperature-dependent thermal-conductivity, κ, measurements on the layered quasi-two-dimensional organic superconductors κ -(BEDT-TTF)2 Cu(NCS)2 and κ -(BEDT-TTF)2 Cu[N(CN)2 ]Br down to 160 mK. The results for κ -(BEDT-TTF)2 Cu(NCS)2 may be consistent with a nodal superconducting (SC) gap structure as indicated by a non-negligible remnant linear contribution when κ / T ∝ T 2 is extrapolated to T = 0 . For κ -(BEDT-TTF)2 Cu[N(CN)2 ]Br, contrary to expectations, higher κ values are observed in the superconducting regime as compared to the normal, high-field state evidencing a dominant phonon contribution to κ in the superconducting state. The strong increase of κ in the normal state below T c for both samples indicates strong electron–phonon scattering. Our results highlight the need for thermal-conductivity measurements performed down to significantly lower temperatures to determine the symmetry of the SC gap.